Life‐history constraints on maximum population growth for loggerhead turtles in the northwest Atlantic. Issue 17 (2nd August 2019) - Hatch, Joshua M.; Haas, Heather L.; Richards, Paul M.; Rose, Kenneth A.
Abstract: Conservation planning for protected species often relies on estimates of life‐history parameters. A commonly used parameter is the instantaneous maximum population growth rate ( r max ) that can be used to limit removals and design recovery targets. Estimation of r max can be challenging because of limited availability of species‐ and population‐specific data and life‐history information. We applied a method proposed by Neil and Lebreton, originally developed for birds, to loggerhead turtles. The method uses age‐at‐first‐reproduction and adult survival to estimate r max . We used a variety of datasets and matrix population models to confirm an allometric assumption required by the method, and to generate estimates of age‐at‐first‐reproduction and adult survival. A meta‐analysis was applied to parameters from reported growth curves, which were then combined with the size distribution of neophyte nesters to derive estimates of age‐at‐first‐reproduction. Adult survival rates were obtained from an existing matrix population model. Monte Carlo simulation was then used to combine the estimates of the allometric coefficients, age‐at‐first‐reproduction, and adult survival to obtain a probability distribution of approximate r max values. Estimated annual maximum population growth rates averaged 0.024, with a mode of 0.017 and a 95% highest density interval of 0.006–0.047. These estimates were similar to values reported by others using different methods and captured the variability in positive, annual change estimates across nesting beach sites for the northwest Atlantic loggerhead population. The use of life‐history parameters has a long history in wildlife and fisheries management and conservation planning. Our estimates of r max, while having some biases and uncertainty, encompassed values presently used in recovery planning for loggerhead turtles and offer additional information for the management of endangered and threatened species. Abstract : A fundamental life‐history parameter in conservation planning is the maximum population growth rate, which can be used to limit removals or design recovery targets. However, estimating the maximum population growth rate can be challenging because of limited availability of species‐ and population‐specific data and life‐history information. We applied a data‐limited approach, developed and applied to birds by Niel and Lebreton (Conservation Biology, 19(3): 826–835, 2005), to the northwest Atlantic (NWA) population of loggerhead turtles ( Caretta caretta ). We estimated a distribution for the maximum population growth rate that encompassed values presently used in the NWA region for recovery planning of loggerhead turtles, using only estimates of age‐at‐first‐reproduction and adult survival.